2021
DOI: 10.1038/s41598-021-02224-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Viscum pleurodesis and video-assisted thoracic surgery (VATS) bullectomy in patients with primary spontaneous pneumothorax

Abstract: Although surgery is the gold standard for treatment of primary spontaneous pneumothorax (PSP), recurrence after surgery remains a concern. This study sought to evaluate the efficacy of simultaneous pleurodesis using Viscum album (VA) extract and video-assisted thoracic surgery (VATS) bullectomy for the treatment of PSP. From March 2016 to June 2020, 175 patients with PSP underwent bullectomy and intraoperative pleurodesis with VA extract at a single institution. All operations were performed through thoracosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In the vast major of cases (n=24), these complications consisted of a protracted air leak (1.7% of the total); 3 cases had a localized pleural effusion without infection indications, 1 case had had postoperative empyema, 1 case, and substantial postoperative bleeding. Numerous studies have demonstrated the superiority of VATS in terms of shorter surgery time and hospital stays, less postoperative pain, less immune system impact, and less recovery time [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…In the vast major of cases (n=24), these complications consisted of a protracted air leak (1.7% of the total); 3 cases had a localized pleural effusion without infection indications, 1 case had had postoperative empyema, 1 case, and substantial postoperative bleeding. Numerous studies have demonstrated the superiority of VATS in terms of shorter surgery time and hospital stays, less postoperative pain, less immune system impact, and less recovery time [24,25] .…”
Section: Discussionmentioning
confidence: 99%